RESEARCHING THE POSSIBILITIES OF USING FOREIGN EXPERIENCE IN IMPROVING FOREIGN ECONOMIC ACTIVITY - Ahmadjonov Ilyosbek (American Journals Publishing, 2023)
The main forms of foreign economic activity of enterprises are foreign trade activities and international cooperation of production. An important role is played by the state regulation of foreign economic activity. State regulation of foreign economic activity is the regulation of foreign trade, investment and other activities in the field of international exchange of goods, information, works, services, results of intellectual activity. This study analyses the impact of international experience on firm economic performance from the organizational learning approach. Moreover, the study explores the double mediating effect of green knowledge and eco-innovation in the relationship between international experience and economic performance. Because the continuous growth of business is what necessarily leads to the enhancement of economic development. The foreign sector has an important role to play in the economy.
Keywords: Foreign economic activity, international exchange of goods, currency, credit, customs, tariff.